Clinical Impact of Systematic Assessment and Psychoeducation in Specialized Treatment of Adolescents with Severe Functional Somatic Disorders: Results from the AHEAD Study - Karen Hansen Kallesøe; Kaare Bro Wellnitz; Eva Ørnbøl; Charlotte Ulrikka Rask (MDPI AG, 2023)
Functional somatic disorders (FSD), characterized by persistent and disabling physical symptoms, are common in adolescents. Diagnostic uncertainty and insufficient illness explanations are proposed perpetuating factors that may constitute barriers for treatment engagement. This study describes the impact of manualized assessment and psychoeducation on diagnostic certainty and various clinical outcomes in adolescents with multi-system FSD. Ninety-one adolescents (15-19 years) received systematic assessment (4 h) and a subsequent psychiatric consultation (1.5 h). Clinical characteristics included self-reported physical health, symptom severity, illness perception, illness-related behavior, and psychological flexibility assessed before and approximately two months after assessment, prior to specialized treatment. Data were analyzed using t-tests. Immediately following assessment, 71 (80.7%) adolescents out of 88 reported a higher diagnostic certainty and 74 (84.1%) reported that attending assessment gave them positive expectations for future treatment. A clinically relevant improvement of physical health was not observed at two months but considerable reductions were seen in symptom severity, illness worry, negative illness perceptions, illness-related limiting behavior, and psychological inflexibility. The results emphasize that systematic assessment and psychoeducation are important in their own right in the specialized treatment of adolescents with severe FSD.